Surface Density of Disk Galaxies in MOND - Antonino Del Popolo; Morgan Le Delliou (Universe, 2023)
In this paper, we extend a paper by Milgrom (2009, MNRAS 398, 1023) dealing with the existence of a quasi-universal surface density for object of all mass and structure, if they are in the Newtonian regime, i.e., that their mean acceleration is larger than MOND typical acceleration <semantics>a0</semantics>. This result is in agreement with Donato et al. (2009)’s results, claiming the existence of a quasi-universal surface density in all masses in galaxies. The Milgrom paper also predicts that objects with mean inner acceleration smaller than the values discussed do not show the quasi-universal behavior of the surface density discussed. In the present paper, we extend the result of Milgrom’s paper, based on a point mass model, considering spiral galaxies, modelled with a double exponential disk. Similar to Milgrom’s results, we find the existence of a universal surface density for galaxies with large surface density, and a different behavior for galaxies having small surface density.